A PARTIAL DEFENSE OF EXTENDED KNOWLEDGE. Issue 1 (October 2014) - Brogaard, Berit
Abstract : The paper starts out by distinguishing two closely related hypotheses about extended cognition. According to the strong hypothesis, there are no intrinsic representations in the brain. This is a version of the extended‐mind view defended by Andy Clark and Richard Menary. On the weak hypothesis, there are intrinsic representations in the brain but some types of cognition, knowledge or memory are constituted by particular types of external devices or environmental factors that extend beyond the skull and perhaps beyond the skin. This type of view was defended, for example, by Andy Clark and David Chalmers. After drawing this distinction and clarifying the notions of causal influence and constitution, I defend the second weaker hypothesis with respect to procedural knowledge and knowledge of action and show why this sort of view supports what we might call a 'situationist‐friendly virtue epistemology'.